Пластичні наліпи на археологічній кераміці - Івашків, Г. (Інститут народознавства НАН України, 2008)
The article explores relief “decorations”, i.e. elements of different shape which can be found on archaeological earthenware, in particular, bowls, beakers, pots, dippers, jugs etc. The relief “decorations” differed in shape (here several kinds may be singled out according to the complexity of form) as well as in the placement (on the rims, mouths, sides). These types of ceramics were a distinctive feature in the Bronze and Iron epochs. Still there is no generalizing critical research on such elements, meant to synthesize major works of this character from different epochs and cultures. The given study of relief elements not only enhances the characteristics of ancient earthenware which combine various means of artistic expression but also in a way reproduces the graphic world of tribes belonging to archaeological cultures.